Keanekaragaman Jenis Burung Di Hutan Pinus Dan Hutan Campuran Muarasipongi Kabupaten Mandailing Natal Sumatera Utara - Muhammad Rohiyan; Agus Setiawan; Elly Lestari Rustiati (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Muarasipongi pine and mixed forests contribute greatly to the biodiversity wildlife. The study of bird species diversity in pine and mixed forests Muarasipongi, to support the preservation and protection efforts on biodiversity especially bird species. This research was conducted on August 2013 by the point count method on Muarasipongi pine and mixed forest then mark and record all the birds over a predetermined period of time before moving to the next point. The data obtained were analyzed and then used to calculate the index of species diversity equality, and community similarity were determined. Observations were made during six repetitions. There are 19 species pine forest, 24 species in the mixed forest and 5 types of birds found in both forest. Total birds found in Muarasipongi 38 species of 20 families. Diversity index (H ') (3.358). The equality index is 0.923, and has a (IS) or Similarity index is worth 0.277 which means that the similarity between the two species is different habitats. Keywords: birds, diversity, index, preservation, protection